جريمة السب و القذف عبر مواقع التواصل الاجتماعي - الفاسي بوزيان; عيفة الطيب; د/ بن عيشوش عمر (جامعة عمار ثليجي الاغواط, 2024)
ملخص باللغة العربية: تناول هذا البحث على دراسة جريمة السب والقذف عبر مواقع التواصل الإجتماعي التي تعد من الجرائم التي تنال من شرف واعتبار الإنسان، فهي إيذاء محرم وقول مجرم معاقب عليه شرعا وقانونا، فهي تعد من جرائم الحدود، وقد شرع الله عز وجل حد القذف لكل من تقوده نفسه الأمارة بالسوء، كما ساير المشرع الجنائي الجزائري الشريعة الإسلامية في تجريم المساس بشرف وكرامة الإنسان وعرضه. الكلمات المفتاحية: السب، القذف الجريمة، مواقع التواصل الإجتماعي This research dealt with studying the crime of insult and slander via social networking sites, which is considered one of the crimes that undermine human honor and dignity. It is forbidden harm and the words of a criminal punishable by law and law. It is considered a hudud crime, and God Almighty has prescribed the punishment for slander for anyone who is led by himself. Emirating evil, as the Algerian criminal legislator went along with Islamic law in criminalizing attacks on human honour, dignity and honor. Keywords: insult, slander, crime, social networking sites Summary in English
دراسة فقهية قانونية